Honorific statuary in the third century AD - Spranger, SKM (2014)
The habit of honouring outstanding individuals with statues was common throughout the Roman Empire. Yet after the end of the Severan reign at the beginning of the third century AD, a decrease in honorific statues is generally assumed to have taken place. This thesis aims to evaluate this hypothesis, focusing specifically on the years AD 222-285. The thesis is assessing the contemporaneous imperial remains for the Roman Empire as a whole and the evidence from four exemplary cities that are particularly conspicuous in their statuary production and display, both before and after the time frame under investigation (Leptis Magna, Athens, Ephesus, Aphrodisias). The purpose is to explore the standards, conventions, and limitations of statuary practice in Roman society in a synthetic and comparative analysis and thereby to evaluate its political and social role during a state of internal and external instability, labelled 'the third century crisis'. By providing concrete figures, the practice of the third century can be juxtaposed with both the antecedent and subsequent centuries and this will facilitate a more coherent insight into the overall development and changes in Roman honorific statuary practice. The results suggest that the assumed decline in the number of statuary installations might have to be re-evaluated. It has become apparent that in order to obtain comparable numbers, the inclusion of imperial family members in any statistical evaluation is indispensable, a factor which has previously been disregarded. A gradual decrease cannot be supported and neither can a decrease in the appreciation of honours.